Rastreamento de polimorfsmos no gene HIOMT e associações com os fenótipos circadianos - Pereira, Danyella Silva; Koike, Bruna Del Vechio; Ribeiro, Amanda de Oliveira [UNESP]; Umemura, Guilherme Silva; Tufik, Sergio; Neto, Mario Pedrazzoli (My University, 2013)
HIOMT is a gene that encodes hydroxyindole-O-methyltransfe-rase, the final enzyme in the melatonin synthesis pathway. As the timing of melatonin synthesis is different for morning and evening people, it is possible that polymorphisms in genes coding for the enzymes which participate in melatonin synthesis can influence this hormone synthesis and release patterns that may result in different circadian outputs. The aim of this study was to search for polymorphisms in the HIOMT gene and to verify possible associations between genetic variations in this gene and circadian phenotypes in a Brazilian population sample. Among the 44 extreme morning and the 48 extreme evening people, ten polymorphisms were found, being two of them not described so far. Haploview analyses showed linkage disequilibrium between pairs of polymorphisms in the promoter B region. Also, the haplotype AG (rs4446909, rs5989681) is associated with evening preference. The analysis of these data indicates that polymorphisms in the HIOMT gene exhibit a possible trend to influence circadian phenotypes in this Brazilian population sample, possibly affecting the rate and/or level of melatonin synthesis.
Screening for polymorphisms in the HIOMT gene and associations with circadian phenotypes
Keywords: Circadian rhythm; Genetics behavorial; Melatonin; Polymorphism genetic